A source book in Indian philosophy - Radhakrishnan, Sarvepalli; Moore, Charles A. (Princeton paperbacks, 1957)
Here are the chief riches of more than 3,000 years of Indian philosophical thought-the ancient Vedas, the Upanisads, the epics, the treatises of the heterodox and orthodox systems, the commentaries of the scholastic period, and the contemporary writings. Introductions and interpretive commentaries are provided.